2013
DOI: 10.1111/ejn.12443
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological properties of enhanced green fluorescent protein (EGFP)‐expressing wide‐field amacrine cells in the ChATEGFP mouse line

Abstract: Mammalian retinas comprise a variety of interneurons, among which amacrine cells represent the largest group, with more than 30 different cell types each exhibiting a rather distinctive morphology and carrying out a unique function in retinal processing. However, many amacrine types have not been studied systematically because, in particular, amacrine cells with large dendritic fields, i.e. wide-field amacrine cells, have a low abundance and are therefore difficult to target. Here, we used a transgenic mouse l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Therefore, there is a possibility that overexpression of tau-GFP may contribute to the retinal neurodegeneration observed. However, the failure of ChAT-Rosa mice to label cholinergic amacrine cells was similar to that observed in ChAT-GFP mice (Haverkamp et al 2009; Knop et al 2014). The ectopic expression of fluorescent proteins in cells driven by the ChAT promoter also occurs in the cortex (von Engelhardt et al 2007) and hippocampus (Yi et al 2015).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Therefore, there is a possibility that overexpression of tau-GFP may contribute to the retinal neurodegeneration observed. However, the failure of ChAT-Rosa mice to label cholinergic amacrine cells was similar to that observed in ChAT-GFP mice (Haverkamp et al 2009; Knop et al 2014). The ectopic expression of fluorescent proteins in cells driven by the ChAT promoter also occurs in the cortex (von Engelhardt et al 2007) and hippocampus (Yi et al 2015).…”
Section: Discussionsupporting
confidence: 64%
“…In contrast, immunostaining for 5-HT3AR was found in synaptic hot spots in sublamina 1 of the inner plexiform layer and was not related to type 5 bipolar cells. Despite these results, the authors concluded that these mouse lines are extremely useful for microelectrode targeting of well-defined retinal neuron types; they have investigated one such transgenic cell type in detail, identifying it as a wide-field ON–OFF gamma-aminobutyric acid (GABA)-containing cell type (Knop et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In salamander, amacrine cells include wide- vs. narrow-field varieties, which generate transient and sustained light responses respectively [19]. By contrast, in mammalian retinas, both transient [2023] and sustained responses [24] have been recorded from wide-field amacrine cells, and also from narrow-field ones [25]. Here, we detected spiking, sustained ON light responses in displaced rat amacrine cells with very diverse field sizes.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast to group 1 and 2 retinas, however, dendritic processes of the CaR expressing inner retinal neurons showed narrow stratification in strata 2, 3, and 4 of the IPL. It has been documented that in both the mouse and the rat starburst-a and starburst-b ACs and WA-2/3 ACs can be accounted for the three CaR positive bands in the IPL (Gábriel and Witkovsky, 1998; Knop et al, 2014). To summarize these above results we conclude, that close relative species displayed similar CaR labels, for example most rodent retinas formed group 3, all carnivore species were in group 1 and the human and squirrel monkey retinas were in group 2.…”
Section: Resultsmentioning
confidence: 99%